Insight on the theropod fauna from the Uberaba Formation (Bauru Group), Minas Gerais State: New megaraptoran specimen from the Late Cretaceous of Brazil - Martinelli, Agustín Guillermo (2013)
The first bony theropod record from the Campanian Uberaba Formation (Bauru Group) is described. It consist of an isolated caudal centrum (CPPLIP 1324) found in the city of Uberaba, Minas Gerais State, Brazil. The amphicoelous centrum posseses a length to height ratio of 1.74, deep elliptical lateral pneumatic foramen representig 26% of the centrum lenght with three main sub-circular air chambers, and camellate internal structure. This combination of features is shared with Aerosteon, Megaraptor, and Orkoraptor from the Late Cretaceous of Argentina and with the Megaraptora indet. from the Sao José do Rio Preto Formation (Bauru Group), Sao Paulo State, allowing us to refer it to the Megaraptora clade (Tetanurae, Neovenatoridae). As such, the new specimen represents the second megaraptoran from the Late Cretaceous of Brazil and provides new information on tail anatomy on this bizarre group.